2021
DOI: 10.1115/1.4052512
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility Versus Feasibility: Optimizing Function Allocation for Accommodation of Heterogeneous Populations

Abstract: Human beings are physically and cognitively variable, leading to a wide array of potential system use cases. To design safe and effective systems for highly heterogeneous populations, engineers must cater to this variability to minimize the chance of error and system failure. This can be a challenge because of the increasing costs associated with providing additional product variety. Most guidance for navigating these trade-offs is intended for late-stage design, when significant resources have been expended, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…For those that do, this may be the first point in the process where they will begin to gain a better understanding of how their users interact with the product and if the product is liked. If this discovery goes poorly, design teams may be forced to iterate back through the process again with a need for severe change (Knisely, and Vaughn-Cooke, 2022). Unlike iterating back through the process to fix small issues in a prototype design, re-designing around an entirely new user perspective can be wildly expensive if there is a large change in scope.…”
Section: Current Methodologies In Functional Analysis and Human-cente...mentioning
confidence: 99%
See 2 more Smart Citations
“…For those that do, this may be the first point in the process where they will begin to gain a better understanding of how their users interact with the product and if the product is liked. If this discovery goes poorly, design teams may be forced to iterate back through the process again with a need for severe change (Knisely, and Vaughn-Cooke, 2022). Unlike iterating back through the process to fix small issues in a prototype design, re-designing around an entirely new user perspective can be wildly expensive if there is a large change in scope.…”
Section: Current Methodologies In Functional Analysis and Human-cente...mentioning
confidence: 99%
“…Studies have shown that these participants feel bogged down, at times, by the process, and the results they produce are often limited as well. (Caldwell et al, 2012;Knisely and Vaughn-Cooke, 2022) Additionally, these methods are challenging for inexperienced engineers to pick up. Students and early-career engineers that are not thoroughly versed in the design process and accompanying terminology may struggle through functional analysis.…”
Section: Critiques Of Functional Analysis and Human-centered Designmentioning
confidence: 99%
See 1 more Smart Citation